Dynamic modeling of spatial parallel mechanism with multi-spherical joint clearances. (18th September 2019) - Chen, Xiulong; Sun, Chenghao
The parallel mechanism has advantages of the high speed, high precision, strong carrying capacity, and high structural rigidity. Most of the previous studies concerning the dynamic modeling focused on planar mechanisms with revolute clearance joints or spatial mechanisms with one spherical joint clearance, while few studies focused on spatial parallel mechanisms with multi-spherical joint clearances. In this article, a general dynamic modeling method for spatial parallel mechanism with multi-spherical joint clearances based on Lagrange multiplier method is proposed. Taking 4universal joint-prismatic joint-spherical joint/universal joint-prismatic joint- universal joint (4UPS-UPU) spatial parallel mechanism as an example, the constraint equations of common kinematic pairs in spatial parallel mechanism, such as universal joint, spherical joint, and prismatic joint, are derived in detail. The dynamic model of the parallel mechanism with two spherical joint clearances combining the Flores contact force model and the LuGre friction model is established. The correctness of model has also been verified by comparing the analysis results of MATLAB with those of ADAMS. It can be seen that dynamic model of spatial parallel mechanism with multi-spherical joint clearances could be easily established by this method, which provides a theoretical reference to establish the dynamic model of other parallel mechanism with multi-clearance in the future.